Is the Articular Cartilage Regeneration Approachable Through Mesenchymal Stem Cells Therapies? - López-Puerta, José María; Zamora-Navas, Plácido; Claros-Gil, Silvia; Rico-Llanos, Gustavo Adolfo; Avedillo, Inés; Andrades-Gómez, José Antonio; Becerra-Ratia, José (InTech, 2013)
oday great hope is set on regenerative medicine in all medical fields. Leland Kaiser introduced the term “Regenerative Medicine” in 1992. He forecasted that a “new branch of medicine will develop that attempts to change the course of chronic diseases and in many instances will regenerate tired and failing organ systems” (Kaiser, 1992). Since then, scientists all over the world try to develop cell-based approaches to regenerate damaged tissues, or even substitute whole organs. Degenerative disease of articular cartilage (AC), generically known as osteoarthritis (OA), is an irreversible evolution process towards terminal articular failure. Due to its high prevalence on population and its socioeconomic impact, this condition is of great concern, and this way more resources and effort are dedicated to the research on its development. Cartilage tissue engineering seeks to combine cells, biomaterial scaffolds, and bioactive signals to create functional tissue replacements to treat cartilage injuries or osteoarthritis.
Keywords: Células madre; Mesenchymal stem cells; Articular cartilage